Strategic use of geotechnical data for maximised value added - Palleske, CK; Kalenchuk, KS; Hume, CD; Bawden, WF (Deep Mining 2017: Eighth International Conference on Deep and High Stress Mining, 2017)
A sound geotechnical database forms the baseline for any geomechanical analysis or mine design. The level of detail of geotechnical information typically increases as a project moves from initial design stages through to construction and operation. This begins with core logging and outcrop mapping, enhanced by line mapping once additional excavation exposures are available. Lab testing, in situ stress testing and geophysical information may also be added to the database. The data collected early in a project often form the basis for decisions regarding mine design, method and sequencing. Once a project reaches the operation stage, the assumptions made about a site geomechanical model during earlier design phases must be verified. This paper discusses how to maximise the use of geotechnical data that is routinely collected at each stage of project development by building an appropriate model for that phase of work. This includes the development of a site-specific ground behaviour model, which allows design criteria to be optimised for the conditions that are actually encountered. The use of ground behaviour data such as damage mapping, pull test results, falls of ground and overbreak for refining the geotechnical model are also discussed.
Keywords: geotechnical ground model; behaviour prediction